Indian chronic kidney disease study: Design and methods. Issue 4 (April 2017) - Kumar, Vivek; Yadav, Ashok Kumar; Gang, Sishir; John, Oommen; Modi, Gopesh K; Ojha, Jai Prakash; Pandey, Rajendra; Parameswaran, Sreejith; Prasad, Narayan; Sahay, Manisha; Varughese, Santosh; Baid‐Agarwal, Seema; et al.
Abstract: Aim: The rate and factors that influence progression of chronic kidney disease (CKD) in developing countries like India are unknown. A pan‐country prospective, observational cohort study is needed to address these knowledge gaps. Methods: The Indian Chronic Kidney Disease (ICKD) study will be a cohort study of approximately 5000 patients with mild to moderate CKD presenting to centres that represent different geographical regions in India. Time to 50% decline in baseline estimated glomerular filtration rate, need of renal replacement therapy or any new cardiovascular disease (CVD) event or death from CVD are the primary end points. Value of Study: This study will provide the opportunity to determine risk factors for CKD progression and development of CVD in Indian subjects and perform international comparisons to determine ethnic and geographical differences. A bio‐repository will provide a chance to discover biomarkers and explore genetic risk factors. Summary at a Glance: This study aims to determine risk factors for CKD progression and CVD development in Indian people through the international comparisons to determine ethnic and geographical differences. Authors also apply the bio‐repository to discover biomarkers and explore genetic risk factors in this study.